Bronislovas Ketarauskas (1905–1978) as the exile author of a textbook of higher mathematics - Banionis, Juozas (Lietuvos matematikos rinkinys, 2008)
B. Ketarauskas successfully finished mathematics studies at Vytautas Magnus University in 1931 and at the end of the World War II retreated to the West, where not only was he distinguished as a talented pedagogue,but in 1947 his „The Basics of Differential and Integral Calculus“ was publishedfor the second time, too. This two-part textbook covered the main topical areas of higher mathematics, i.e., mathematical limits, derivatives, differentials, definite and indefinite integrals. The text in the book abounds in illustrative material. It enables the student to obtain essential knowledge in higher mathematics. Presumably, this textbook can also be useful in nowadays.
Keywords: Lithuanian exile; education; differential and integral calculation